(3JaYjd GdJShjb GdeUQaj dehGLgI BKGQ GdLGJS (B/s - (3SGei, CMeO eQGOs ((3GdbGgQI(B: s (3GdecJH GdYQHj ddeYGQa(B, s, 2007)
(3jVe GdLGJS hGdNOeGJ GdeUQajI, GdJShjb GdeUQaj hOQGSI GdYedGA hGdShb, JaYjd GdJShjb GdeUQaj hJMbjb QVG GdYejd, GOGQI GdfTGW GdJShjbj aj GdHfcs
(3HjHdjhZQGajG(B: (3U(B.297s
Keywords: (3GdGOGQIs; (3GdHfhcs; (3GdJShjbs